Thermodynamics and Kinetics of Adoption of Ag (I) on Paramagnetic Silica Rice Husk Ash Surface - Wardian Antoni; Saprini Hamdiani; Siti Raudhatul Kamali (Acta Chimica Asiana, 2019)
Synthesis of paramagnetic silica from rice husk ash has been carried out as an adsorbent for heavy metal Ag (I). This study tried to synthesis and characterized the thermodynamics and kinetics behaviour of paramagnetic silica from the husk ash as metal adsorbent Ag (I). Determination of optimal conditions for adsorption of metal ions Ag (I) is carried out by varying the pH, concentration, and contact time of the adsorbent. The results showed that the optimum pH was at pH 3, optimal concentration Ag(I) of 350 ppm and optimal contact time of 90 minutes. At optimal conditions, paramagnetic silica adsorption capacity for metal ion Ag (I) is 323.62 mg/g. The isotherm model that is suitable for paramagnetic silica is the Freundlich isotherm model. The kinetic model that is suitable for paramagnetic silica is the Pseudo Order 2 kinetic model.